N-terminal domains of cardiac myosin binding protein-C cooperatively activate the thin filament. - Risi, Cristina (Structure, 2018)
Muscle contraction relies on interaction between myosin-based thick filaments and actin-based thin filaments. Myosin binding protein-C (MyBP-C) is a key regulator of actomyosin interactions. Recent studies established that the N’-terminal domains (NTDs) of MyBP-C can either activate or inhibit thin filaments, but the mechanism of their collective action is poorly understood. Cardiac MyBP-C (cMyBP-C) harbors an extra NTD which is absent in skeletal isoforms of MyBP-C and its role in regulation of cardiac contraction is unknown. Here we show that the first two domains of human cMyPB-C (i.e., C0 and C1) cooperate to activate the thin filament. We demonstrate that C1 interacts with tropomyosin via a positively charged loop and that this interaction, stabilized by the C0 domain, is required for thin filament activation by cMyBP-C. Our data reveal a mechanism by which cMyBP-C can modulate cardiac contraction and demonstrate a function of the C0 domain.